Analysys of Variation of Soaking Duration of Asphalt Concrete Wearing Course (AC-WC) Mixture Using Natural Rubber Modified Asphalt Against Indirect Tensile Strength Value (ITS) - Saleh, Alfian; Siregar, Iwan Ananda; Anggraini, Muthia (Universitas Negeri Semarang, 2024)
Natural rubber asphalt modification is the result of the mixing of asphalt with natural rubber plus chemical additives of vulcanization (sulfur) that are mixed into one in a hot state. The addition of natural rubber makes the asphalt more elastic and able to withstand loads from heavier vehicles, more heat-resistant, and more adhesive to aggregates that make the road surface more resistant to cracks and holes. The research aims to analyze indirect tensile strength values in asphalt-modified natural rubber. The research method is a laboratory experimental study referring to SNI 6753:2015, with immersion variations of ½ hour, 24 hours, 48 hours, and 72 hours. The results of the study were indirect tensile strength values at congestion for 12 hours, 24 hours, 48 hours, and 72 hours in a row of 459,752 KPa, 427,571 KPa, 379,771 KPa, and 379,971 KPa. The resulting tensile strength ratio for each variation is 100%, 92.98%, 82.59%, and 75.52%. The study concluded that the tensile strength ratio at submersion for ½ hours, 24 hours, and 48 hours meets the requirements of the AASTHO T-283 specification.